Triplet-Energy Quenching Functions of Antioxidant Molecules - Carlos Angelé-Martínez; Leticia Christina Pires Goncalves; Sanjay Premi; Felipe A. Augusto; Meg A. Palmatier; Saroj K. Amar; Douglas E. Brash (MDPI AG, 2022)
UV-like DNA damage is created in the dark by chemiexcitation, in which UV-activated enzymes generate reactive oxygen and nitrogen species that create a dioxetane on melanin. Thermal cleavage creates an electronically excited triplet-state carbonyl whose high energy transfers to DNA. Screening natural compounds for the ability to quench this energy identified polyenes, polyphenols, mycosporine-like amino acids, and related compounds better known as antioxidants. To eliminate false positives such as ROS and RNS scavengers, we then used the generator of triplet-state acetone, tetramethyl-1,2-dioxetane (TMD), to excite the triplet-energy reporter 9,10-dibromoanthracene-2-sulfonate (DBAS). Quenching measured as reduction in DBAS luminescence revealed three clusters of 50% inhibitory concentration, ~50 μM, 200-500 μM, and >600 μM, with the former including sorbate, ferulic acid, and resveratrol. Representative triplet-state quenchers prevented chemiexcitation-induced "dark" cyclobutane pyrimidine dimers (dCPD) in DNA and in UVA-irradiated melanocytes. We conclude that (i) the delocalized pi electron cloud that stabilizes the electron-donating activity of many common antioxidants allows the same molecule to prevent an electronically excited species from transferring its triplet-state energy to targets such as DNA and (ii) the most effective class of triplet-state quenchers appear to operate by energy diversion instead of electron donation and dissipate that energy by isomerization.